EFEK PENEMBAKAN LASERPUNKTUR PADA TITIK OVA BEBEK MOJOSARI JANTAN TERHADAP JUMLAH SEL SERTOLI DAN LEYDIG - Adikara, Yuanara Augusta Rahmat; Utama, Suzanita; Yudaniayanti, Ira Sari; R.T.S Adikara, R.T.S Adikara; Samik, Abdul; Hestianah, Eka Pramyrtha (Universitas Airlangga, 2018)
Demand for eggs and duck meat lately increased along with the increasing interest of the community to consume eggs and duck meat. Due to that reason researcher try to find the best way to enhance the reproductive ability of livestock., which is in this research by laserpuncture shot. This research used 3 treatments: the control group, first treatment with laserpuncture shot dose of 0.2 J, second treatment with laserpuncture shot dose of 0.4 J. Data was analyzed with ANOVA and further test by Duncan Multiple Range Test. Research result proved that Laserpuncture shot with dose of 0.2 J and 0.4 J decrease the number of sertoli and leydig cells.